The tetrapod fauna of the upper Permian Naobaogou Formation of China: 5. Caodeyao liuyufengi gen. et sp. nov., a new peculiar therocephalian - Liu, Jun (2020)
The upper Permian Naobaogou Formation has been the goal of recent contributions that notably increased the knowledge of its terrestrial vertebrate fauna and unravelled a hidden late Permian therocephalian diversity in China. Two very different species of therocephalians have been documented in the Naobaogou Formation and they were recovered as basal akidnognathids in cladistic analyses. In this contribution we describe Caodeyao liuyufengi gen. et sp. nov., represented by a partial skull and mandible, and a humerus. The new taxon features a short, high snout and a wide temporal opening with the coronoid process of the mandible separated by a wide space medially to the zygomatic arch. The latter feature is only recognized in the Russian therocephalian Purlovia maxima and it is also characteristic of non-mammaliaform cynodonts. Phylogenetic analysis indicates a close relationship of the new Chinese taxon with Purlovia maxima, producing a monophyletic Laurasian group in therocephalian phylogeny. With the representation of three different species, the Naobaogou Formation is now the most prolific unit documenting therocephalian late Permian diversity in China.